Angular dependence of the strong-field ionization measured in randomly oriented hydrogen molecules - Magrakvelidze, Maia; He, Feng; De, Sankar; Bocharova, Irina; Ray, Dipanwita; Thumm, Uwe; Litvinyuk, I. V. (My University, 2009)
We employed electron-ion coincidence momentum spectroscopy to measure the relative angle between an emitted electron and a deuteron resulting from field dissociation of the molecular ion produced by a circularly polarized pulse. We deduced the angular dependence of the molecular ionization probability without having to align the molecules first. We determined that with 50 fs pulses of 1850 nm wavelength and 2×1014 W/cm2 intensity neutral D2 molecules are 1.15 times more likely to be ionized when the laser electric field is parallel to the molecular axis than for the perpendicular orientation, in excellent agreement with our ab initio theoretical model. Our results also agree with predictions of the molecular Ammosov-Delone-Krainov (mo-ADK) theory, as well as those of a similar experiment performed with 800 nm pulses of comparable intensity and duration on H2 molecules.